(untitled) (International Seven Journal of Multidisciplinary, 2023)
This study examines the importance of strategic planning in private security management, linking risk management, contractual governance, technology and human capital development, with a focus on practices that improve operational effectiveness and service continuity, a documentary and analytical review identified patterns connecting formal plans to higher compliance rates and coordinated incident response, the conclusions stress the need for initial diagnostics, well-defined indicators, technical contractual clauses and training programs, as well as the integration of technological investments with governance models that ensure interoperability and maintenance, it is recommended to institutionalize control panels, oversight committees and regular review cycles to support budgetary and operational decisions based on evidence, measures that contribute to organizational resilience, service quality and institutional credibility in the national context.